Family dynamics in the management of dengue in Villavicencio, Meta (Boletín Semillero de Investigación en Familia, 2022)
Introduction: the main risk factors for the proliferation of dengue among families are inappropriate behaviors, ignorance and inadequate waste management. Objective: to identify family dynamics in the management of dengue in families in the city of Villavicencio, Meta. Materials and methods: Qualitative research, with a focused ethnography tool. The selected families were those that had a member of their family with a confirmed case of Dengue, in the last 6 months. The semi-structured interview, sociodemographic survey, observation, and field diary were used as instruments. Results: The following categories were identified: knowledge of the disease, community actions, family interactions in health care. Conclusions: The research indicates a greater presence of female leadership. Families carry out practices in their homes for vector control. In the community actions, low interest is evidenced, the families recognize that the health institutions have carried out education on Dengue. Among the risk behaviors is that a large part preferred to self-medicate.
Keywords: dengue; family; practices.